Perancangan Media Promosi "Café Nomu9 Bites & Beverages" Sebagai Penguat Brand di Kota Malang - Fajar Akbar Alfatah; Adita Ayu Kusumasari (MAVIS : Jurnal Desain Komunikasi Visual, 2021)
The food and beverage industry are now growing and varied starting from the price also the price as well. This causes business competition in this field Increases consumer prices in determining and selecting products needed by media promotions for companies to be able to compete with other companies. Therefore, the author of promotional media for Nomu9 Bites & Beverage cafe can compete with new cafes in Malang through social media in the form of videos on the Instagram and Youtube platforms. Social media was chosen because many people use it. It also cheap and measurable promotional media. The design model uses Sadjiman Ebdi Sanyoto, which starts with the background of the problem, discusses the data source, then passes the synthesis, the design concept, the design process, and the final design. The software used in the process of making this promotional media include Adobe Premiere, Adobe After Effects, Adobe Photoshop, and Adobe Lightroom. Commercial ad format Mp4 has a resolution of 1920x1080 and is 1 minute long. Instagram story format Mp4, has a resolution of 1080x1920 (vertical) with a duration of 15 seconds. Supporting media include: Mp4 photo slideshow format, has a resolution of 1080x1920 (vertical) and has a duration of 60 seconds. The next writer is expected to be able to discuss the same with different media.